Power quality events recognition using enhanced empirical mode decomposition and optimized extreme learning machine. (May 2022) - Samanta, Indu Sekhar; Rout, Pravat Kumar; Swain, Kunjabihari; Cherukuri, Murthy; Mishra, Satyasis
Highlights: Empirical Mode Decomposition technique is used for feature extraction to detect power quality disturbances. Kriging interpolation-based Empirical Mode Decomposition enhances the performance. Extreme Learning Machine is used for the classification of power quality disturbances. The robustness of the Extreme Learning Machine is enhanced by the Symbiotic Organism Search Optimization technique. Validated the efficacy of the proposed approach on the hardware experimental setup. Abstract: In this paper, a novel approach based on Empirical Mode Decomposition (EMD) and an Extreme Learning Machine (ELM) for the detection and classification of Power Quality Events (PQEs) is proposed. The EMD technique is used for computing the prominent features required to characterize the PQE signals. A down-sampled Kriging Interpolation (KI) based EMD is suggested to enhance the performance of the EMD operation in terms of accuracy and speed. The ELM is applied for the classification of Power Quality Disturbances (PQDs), considering all the derived features through the KI-EMD approach. Symbiotic Organism Search (SOS) optimization technique is applied to enhance the performance and robustness of ELM by optimally computing the values of the system parameters. The performance of the proposed approach is justified with test cases under diverse noise conditions. Comparative results and analysis are provided to show an improvement of 2-5% in terms of accuracy, speed, and robustness compared to other conventional methods. Experimental results validate the efficacy of the proposed approach under real-time conditions. Graphical abstract: Image, graphical abstract